Godly Love: Impediments and Possibilities - Lee, Matthew T.; Yong, Amos (Lexington Books, 2012)
Godly Love: Impediments and Possibilities examines the theory of “Godly Love,” understood as including a vertical axis denoting the love of God and a horizontal axis involving the love of others, is at the core of a new field of research that studies how divine love influences the love of others and vice-versa. It is a multi-disciplinary research program into the benevolent expressions of the Great Commandment of the Christian tradition involving the theological and social sciences. Theological and social scientific essays ask why there is not more Godly Love in this world and what might be done to change the situation. This book focuses on the problems confronting, challenging, prohibiting, and perhaps even resisting the concrete expression of Godly Love in the world, utilizing a range of theological and especially social scientific methodologies.